Effect of Company Size and Profitability on Audit Delay - Ari Bramasto; Muhamad Iqbal Adrian; Dudi Hendaryan; Siti Khadzartsenya (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
This study is a quantitative study, which aims to determine: 1) The magnitude of the influence of Company Size on Audit delay on Property and Real Estate sector companies in Indonesia, 2) The magnitude of the effect of Profitability on Audit delay on Property and Real Estate sector companies in Indonesia, and 3) The influence of Company Size and Profitability simultaneously affects audit delays on Property and Real Estate sector companies in Indonesia. The sampling technique used is non-probability sampling with the purposive sampling method, so that 19 companies were obtained for 5 years with a total of 95 analysis units. The tests carried out in this study include descriptive statistics, validity tests, reliability tests, classical assumption tests (normality tests, heteroskedasticity tests and, multicolonierity tests), multiple linear regression tests, correlation coefficient tests, determination coefficient tests, t tests, and f tests processed using the help of SPSS (Statistical Product and Service Solutions) software for Windows version 26. The results of this study show that 1) Company Size affects audit delays in property and real estate sector companies in Indonesia. 2) Profitability affects audit delays in property and real estate sector companies in Indonesia. 3) Company Size and Profitability simultaneously affect audit delays in property and real estate sector companies in Indonesia.